2018
DOI: 10.15835/buasvmcn-vm:2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

First Record of West Nile Virus Specific Seroconversion in Dogs From Eastern Romania

Abstract: West Nile virus (WNV) infection causes diseases that vary in intensity from asymptomatic to fatal encephalitis in humans and animals. The etiological agent is a Flavivirus belonging to Japanesse Encephalitis complex. This zoonotic virus is maintained in nature in an enzootic cycle between mosquitoes and birds as amplifying hosts. Except birds, a wide variety of animals develop seroconversion caused by infection, and previous studies indicated that dogs may be considered as sentinel for WNV. The importance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…As demonstrated previously [66], mosquito-based surveillance allows non-invasive blood-sampling from free-roaming vertebrate hosts (e.g., feral horse) and from species which are rare or have a cryptic behavior (e.g., raccoon dog (Nyctereutes procyonoides), European mink (Mustela lutreola), Eurasian otter (Lutra lutra) or Golden jackal (Canis aureus)). This study supports previous studies, which identified horses and dogs as suitable sentinel species for WNV [53,54]. WNV seroprevalence in dogs (6.3%) and horses (3.1%) was similar to conventional sampling of the species in different areas with WNV activity [67][68][69].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As demonstrated previously [66], mosquito-based surveillance allows non-invasive blood-sampling from free-roaming vertebrate hosts (e.g., feral horse) and from species which are rare or have a cryptic behavior (e.g., raccoon dog (Nyctereutes procyonoides), European mink (Mustela lutreola), Eurasian otter (Lutra lutra) or Golden jackal (Canis aureus)). This study supports previous studies, which identified horses and dogs as suitable sentinel species for WNV [53,54]. WNV seroprevalence in dogs (6.3%) and horses (3.1%) was similar to conventional sampling of the species in different areas with WNV activity [67][68][69].…”
Section: Discussionsupporting
confidence: 89%
“…Horse-, human-, dog-and bird-derived blood meals were tested for WNV-specific IgG/IgY, using an indirect immunofluorescence (IIF) assay as described previously [52]. Host species were selected, which are important amplifying hosts (bird), known to become critically ill from WNV infections (human, horse) or were previously identified to be suitable sentinel species for WNV (dog, horse) [6,7,53,54]. In brief, Vero cells infected with WNV NY99 were seeded on microscope slides with 12 reaction wells (Marienfeld, Lauda-Königshofen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The epidemiological data showed that the EEC strains dominate transmission in Romania from 2010-2015 in mosquitoes collected in the Danube Delta [ 41 ] and Bucharest while CSEC strains were detected from 2015 onwards and had replaced earlier EEC lineage 2 strains by 2016 [ 51 ]. Lineage 2 strains had not been evidenced previously in Iași county, although WNV infections in humans are reported annually, and sustained WNV circulation has been evidenced through prevalence studies in horses [ 20 , 42 ] and dogs [ 42 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a dynamic circulation sustained by the local evolution and transit of migratory bird hosts between Africa and Eurasia. Over the past few years, there has been an increasing number of serological and genomic studies on WNV epidemiology in southeast Europe [ 18 , 20 , 21 , 22 , 23 , 24 ]. However, there is no information about the impact of WNV on human health in Kosovo, while only scarce data are available from surveillance of animal hosts [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%